Effects of interaction of biochar and nitrogen fertilizer on growth, yield and yield components of soybean (Bangladesh Journal of Botany, 2019)
Effects of the interaction of biochar and nitrogen fertilizer on the growth, yield and yield components of soybean were studied in cylindrical tube cultivation. The results showed that proper application of biochar promoted dry matter accumulation and LAI regulation of individual plant, and the regulating effect was greater in the later stage of growth than in the early stage. The dry matter weight per plant and LAI were the highest in C1 treatment with different amount of biochar application. However, with the further increase of the amount of carbon application, the dry matter weight per plant and LAI decreased gradually. The plant height of soybean was reduced by the application of biochar. 750 kg/hm2 of biochar and 42 kg/hm2 of nitrogen were found to be the best combinations for high yield of soybean and the theoretical yield was found to be 3546.9 kg/hm2. The combination of biochar and nitrogen fertilizer affects yield mainly by regulating the number of seed per plant.